Assessment of the as-sintered surfaces of ceramic components additively manufactured by vat Photopolymerization (CerAMVPP) - Nadine Lorenz; Uwe Scheithauer; Eric Schwarzer-Fischer; Sindy Mosch; Martin Propst; Jan Sieder-Katzmann; Christian Bach (Open Ceramics)
The aim of this work was to gain an initial impression of the surface quality that can be achieved with additively manufactured ceramic components. For this purpose, an assessment body was generated, which has partially double-curved surfaces that can be scanned using a confocal microscope. After manufacturing using Vat Photopolymerization for ceramic components (CerAM VPP) with a commercial alumina suspension (Lithalox 350, Lithoz, Vienna, AUT) and thermal processing, the respective surface was measured at four different geometric areas. For evaluation, line sections were extracted to calculate Ra values as well as to determine Sa values for surfaces. Ra and Sa values were determined in all areas, reaching always values below 2.5 μm. The surface quality is therefore an order of magnitude lower than that of typical metallic AM components.